REKONSTRUKSI SISTEM PENGELOLAAN RUMAH DETENSI IMIGRASI MELALUI PENDEKATAN MANAJEMEN RISIKO DALAM MEWUJUDKAN PENEGAKAN HUKUM KEIMIGRASIAN YANG EFEKTIF - Rafael Yohada; Besse Hartati; Tony Mirwanto (STKIP Subang, 2026)
The Immigration Detention House (Rumah Detensi Imigrasi/Rudenim) plays a strategic role in implementing administrative immigration measures against foreign nationals who are detained pending deportation, repatriation, or the resolution of their immigration status. However, the current management system of Immigration Detention Houses in Indonesia remains predominantly administrative and has not incorporated a risk management approach as the basis for decision-making regarding detainee placement, supervision, and treatment. This condition has limited the effectiveness of detention management, particularly considering the diverse characteristics, security risks, and supervisory needs of detainees. This study aims to examine the existing management system of Immigration Detention Houses and formulate a reconstructed management model based on risk management principles to strengthen effective immigration law enforcement. This research employs normative legal research using statutory, conceptual, and comparative approaches. Legal materials were collected through library research and analyzed qualitatively using descriptive-prescriptive methods. The findings indicate that the current legal framework does not integrate risk management principles into the governance of Immigration Detention Houses, resulting in detainee classification, placement, and supervision being conducted primarily through administrative considerations. This study proposes a reconstructed management system incorporating risk identification, risk analysis, risk evaluation, risk treatment, and continuous monitoring as the foundation for detention management. The proposed model is expected to improve the effectiveness of immigration law enforcement, optimize institutional resources, strengthen the protection of human rights, and establish an adaptive, accountable, and risk-based governance system for Immigration Detention Houses.